Interconnection Between Senior Preschooler‘S Prior Knowledge On Chess And Divergent Thinking - Amiraghyan, M. G. (Մանկավարժ հրատ․)
The article discusses the issue of proper organization of children‘s developmental process during learning, when understanding of the presented material, its reconstruction practical application becomes important. From this, children's prior knowledge play an important role, which is also essential in perceiving chess. In the article, on the one hand, we referred to the methodology of the formation of senior preschoolers‘ (5-6 years old) prior knowledge on chess, emphasizing its investment in the whole pedagogical process of preschool educational institutions (lessons on preschool educational methodologies, games, various work with children, electronic game-tasks), on the other hand, the impact of chess prior knowledge on children's development process, where the transition from the ''zone of actual into proximal development" is essential in the acquisition of knowledge, abilities, skills, a new level of development. In this context prior knowledge is connected with the components of intellect. Հոդվածում քննարկվում է ուսումնադաստիարակչական գործընթացում նախադպրոցական տարիքի երեխաների զարգացման կազմակերպման հարցը, որտեղ կարևոր գործոն է նախագիտելիքը։ Վերջինս էական է նաև շախմատ խաղը յուրացնելու համարֈ Այստեղից էլ, մի կողմից, անդրադարձել ենք ավագ նախադպրոցականների (5-6 տարեկան) շախմատային նախագիտելիքի ձևավորման խնդրին, ընդգծելով դրա ներմուծումը նախադպրոցական ուսումնական հաստատությունների մանկավարժական գործընթացում (տարբեր մեթոդիկաներից կազմակերպվող պարապմունքներ, խաղեր, տարատեսակ աշխատանքներ, էլեկտրոնային խաղ-առաջադրանքներ), մյուս կողմից, շախմատային նախագիտելիքի ազդեցությունը զարգացման գործընթացի վրա՝ ապահովելով անցումն իրական զարգացման գոտուց դեպի մերձական՝ խթանելով երեխայի հնարավոր զարգացումը։ В статье рассматривается вопрос организации развития дошкольников в образовательном процессе, где предварительные знания являются важным фактором. Последнее также необходимо для овладения шахматной игрой. Отсюда, с одной стороны, мы затронули вопрос развития предварительных знаний по шахматам у старших дошкольников (5-6 лет), сделав акцент на их внедрении в педагогический процесс дошкольных образовательных учреждений (занятия, игры, электронные игры-задания), с другой стороны, влияние шахматных предварительных знаний на процесс развития, обеспечивающих переход из зоны «актуального развития» в «ближайшую», стимулируя возможное развитие ребенка.
Keywords: Chess